Anti‐inflammatory effects of eriocitrin against the dextran sulfate sodium–induced experimental colitis in murine model. Issue 11 (8th October 2019) - Guo, Gang; Shi, Wen; Shi, Feiyu; Gong, Wenqing; Li, Fanni; Zhou, Guangju; She, Junjun
Abstract: Inflammatory bowel disease (IBD) is a continual ailment condition which engrosses the entire alimentary canal. The IBD can be primarily distinguished into two forms, ulcerative colitis, and Crohn's disease. The major symptoms of IBD include pustules or abscesses, severe abdominal pain, diarrhea, fistula, and stenosis, which may directly affect the patient's quality of life. A variety of mediators can stimulate the circumstances of IBD, some examples include infections by microbes such as bacteria, perturbation of the immune system and the surrounding environment of the intestines. Severe colitis was stimulated in the experimental animals through administering 4% dextran sulfate sodium (DSS) which is mixed in water ad libitum for 6 days. Eriocitrin (30 mg/kg) was then administered to the experimental animals followed by the induction of severe colitis to evaluate the therapeutic prospective of eriocitrin against the colon inflammation stimulated by DSS. In this study, eriocitrin (30 mg/kg) demonstrated significant ( P  < .05) attenuation activity against the DSS‐stimulated severe colitis in experimental animals. Eriocitrin counteracted all of the clinical deleterious effects induced by DSS, such as body‐weight loss, colon shortening, histopathological injury, accretion of infiltrated inflammatory cells at the inflamed region and the secretion of inflammatory cytokines. The results clearly showed that eriocitrin effectively attenuated DSS‐induced acute colitis in experimental animals.